The Development of Management Model to Improve the Quality of Vocational Education Teachers Under the Office of Vocational Education Commission Chonburi - Thaledon, Sriphloi; Kawmongkon, Songyos; Dechhome, Patchara (Arts of Management Journal, 2024)
The purpose of this research was to develop a management model to improve the quality of vocational education teachers under the Office of Vocational Education Commission in Chonburi. The research procedure was divided into three steps: Step 1: Study the conditions of management to improve the quality of vocational education teachers under the Office of Vocational Education Commission Chonburi. Data were collected from 244 administrators and teachers. And key informants through in-depth interviews with nine experts. Step 2: Create and examine a management model to improve the quality of vocational education teachers under the Office of Vocational Education Commission, Chonburi by the administrator of the Bureau of Personnel Competency Development, the administrator of Rajamangala University of Technology Thanyaburi, and the administrators of vocational education, totaling 10 people. Step 3: Evaluation of the feasibility and utility of a management model to improve the quality of vocational education teachers under the Office of Vocational Education Commission Chonburi by the college director, deputy director, and teachers who were head of department at Pattaya Technical College, totaling 40 people. The research instruments were a semi-structured interview form, a questionnaire, and an evaluation form. Quantitative data were analyzed by a computer program, whereas quality data were analyzed using a content analysis technique. The statistics used for data analysis were mean, standard deviation, exploratory factor analysis, confirmatory factor analysis, and chi-square. The research found that the development of a management model to improve the quality of vocational education teachers under the Office of Vocational Education Commission Chonburi consists of seven main components: 1) Learning management development; 2) Coaching; 3) Bilateral vocational education management; 4) Planner; 5) Creation of innovation; 6) Learning community; and 7) Management process (POCLCE) consists of planning, organizing, coordinating, leading, controlling, and evaluating. The results of the model evaluation in terms of accuracy, propriety, feasibility, and utility overall subcomponents and all indicators were consistent (p-value >.05).